(untitled) (Academicia Globe: Inderscience Research, 2022)
The contemporary times have witnessed an exponential growth and prominence of blockchain, with many researchers terming this innovation as a universal technology having practical applications in almost every aspect of human life. In its short life it has been vividly explored that how this technology could leave a lasting impression on number of industries. The undertaken survey is an attempt to unfold a comprehensive and a systematic review that answers the question of how the blockchain could be utilized as a service for various applications within present days information systems. This survey also provides the reader with a deeper and more intuitive view on how this technology is helpful in securing and managing today’s information system. It includes several examples of blockchain applications and studies put forward by various members of research community and their contribution in different scenarios. Moreover, it has been established that contemporary cloud- and edge-computing and structure of blockchain are paramount in sanctioning general adaption of blockchain as a technology for novel actors in today’s world market.